2020
DOI: 10.3390/su12051971
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Driver Drowsiness: From Causes to Effects

Abstract: Drowsiness and fatigue are major safety issues that cannot be measured directly. Their measurements are sustained on indirect parameters such as the effects on driving performance, changes in physiological states, and subjective measures. We divided this study into two distinct lines. First, we wanted to find if any driver’s physiological characteristic, habit, or recent event could interfere with the results. Second, we aimed to analyze the effects of subjective sleepiness on driving behavior. On driving simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 34 publications
2
18
1
Order By: Relevance
“…The transition from awake to asleep is recognized as sleep onset (SO) [ 1 ], commonly known as drowsiness. Driver drowsiness results in over 20% of road accidents [ 2 , 3 ], reported as one of the leading causes of road fatalities. The most common factors associated with driver drowsiness are sleep deprivation, duration of driving, monotonous environments, drug and alcohol use, and chronic sleepiness [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transition from awake to asleep is recognized as sleep onset (SO) [ 1 ], commonly known as drowsiness. Driver drowsiness results in over 20% of road accidents [ 2 , 3 ], reported as one of the leading causes of road fatalities. The most common factors associated with driver drowsiness are sleep deprivation, duration of driving, monotonous environments, drug and alcohol use, and chronic sleepiness [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are not surprising because our physiological clock prompts sleep at those moments. Recent studies have produced large amounts of evidence focusing their fundamental perspective and potential applications related to driver drowsiness and alertness levels [21][22][23]. New challenges incorporate not only detecting drowsiness but also predicting the driver's state in upcoming moments by predicting future values following the trends and environment variables.…”
Section: Introductionmentioning
confidence: 99%
“…Transportation is one of the most important areas in many sectors. In the transportation industry, fatigue in truck drivers is generally identified as the main safety issue because it has consistently been linked to road crashes [1][2][3][4][5][6]. A transportation department study from the United States reported that three independent studies identified lack of alertness or driving fatigue as one of the main reasons for serious accidents [3].…”
Section: Introductionmentioning
confidence: 99%